The international bibliography of rice research : (Library and Documentation Center, International Rice Research Institute, 1982)
This bibliography is a continuation of the International Bibliography of Rice Research, 1951-1960, and the 1961-1980 Supplements. It contains references published in 1981, plus those published from 1971 to 1980 which were not included in the respective supplements